Macronutrient and micronutrient intakes of children in Oklahoma child-care centres, USA. Issue 8 (17th August 2015) - Rasbold, Andrea H; Adamiec, Ruth; Anderson, Michael P; Campbell, Janis E; Horm, Diane M; Sitton, Leslie K; Sisson, Susan B
Abstract: Objective: To determine macronutrients and micronutrients in foods served to and consumed by children at child-care centres in Oklahoma, USA and compare them with Dietary Reference Intakes (DRI). Design: Observed lunch nutrients compared with one-third of the age-based DRI (for 1–3 years-olds and 4–8-year-olds). Settings: Oklahoma child-care centres ( n 25), USA. Subjects: Children aged 3–5 years ( n 415). Results: Regarding macronutrients, children were served 1782 (sd 686) kJ (426 (sd 164) kcal), 22·0 (sd 9·0) g protein, 51·5 (sd 20·4) g carbohydrate and 30·7 (sd 8·7) % total fat; they consumed 1305 (sd 669) kJ (312 (sd 160 kcal), 16·0 (sd 9·1) g protein, 37·6 (sd 18·5) g carbohydrate and 28·9 (sd 10·6) % total fat. For both age-based DRI: served energy (22–33 % of children), protein and carbohydrate exceeded; consumed energy (7–13 % of children) and protein exceeded, while carbohydrate was inadequate. Regarding micronutrients, for both age-based DRI: served Mg (65·9 (sd 24·7) mg), Zn (3·8 (sd 11·8) mg), vitamin A (249·9 (sd 228·3) μg) and folate (71·9 (sd 40·1) µg) exceeded; vitamin E (1·4 (sd 2·1) mg) was inadequate; served Fe (2·8 (sd 1·8) mg) exceeded only in 1–3-year-olds. Consumed folate (48·3 (sd 38·4) µg) met; Ca (259·4 (sd 146·2) mg) and Zn (2·3 (sd 3·0) mg) exceeded for 1–3-year-olds, but were inadequate for 4–8-year-olds. For both age-based DRI: consumed Fe (1·9 (sd 1·2) mg) and vitamin E (1·0 (sd 1·7) mg) were inadequate; Mg (47·2 (sd 21·8) mg) and vitamin A (155·0 (sd 126·5) µg) exceeded. Conclusions: Lunch at child-care centres was twice the age-based DRI for consumed protein, while energy and carbohydrate were inadequate. Areas of improvement for micronutrients pertain to Fe and vitamin E for all children; Ca, Zn, vitamin E and folate for older pre-schoolers. Adequate nutrients are essential for development and the study reveals where public health nutrition experts, policy makers and care providers should focus to improve the nutrient density of foods.